THE IMPACT OF REDUCING THE STATE'S SHARE IN THE ECONOMY ON WELFARE (American Journal of Business Management, Economics and Banking, 2025)
This article analyzes the impact of reducing the state’s share in the economy on public welfare from both theoretical and practical perspectives. Based on scientific sources, it examines how a decrease in government participation can activate market mechanisms, improve the competitive environment, stimulate private sector development, and enhance the efficient use of resources. At the same time, the article discusses the potential risks of rapid and uncontrolled reduction of the state’s role, including increased social inequality, unemployment, and challenges in strategic sectors. The findings emphasize the necessity of a gradual and balanced approach to optimizing the state’s share in the economy.